Genetic counselors' perceptions of uncertainty in pretest counseling for genomic sequencing: A qualitative study. Issue 2 (11th February 2019) - Park, Jessica; Zayhowski, Kimberly; Newson, Ainsley J.; Ormond, Kelly E.
Abstract: Increased usage of exome and genome sequencing has made uncertainties associated with genomic sequencing methods more prevalent within medicine. Current research focuses on patients' perceptions of uncertainty related to genomic sequencing, but there is limited knowledge of the perspectives of providers. The aim of this study was to explore how professionals in genomics perceive uncertainties involved in genomic sequencing, and if or how this impacts their approach to pretest counseling. We performed 20 semi‐structured interviews with genetic counselors in the United States and Canada who provide pretest genetic counseling for genomic sequencing. Interviews explored participating genetic counselors' views of uncertainty regarding genomic sequencing, how they classify it, how it manifests, and how they manage it during pretest counseling. Thematic analysis showed that genetic counselors acknowledge concepts of uncertainty that map to existing frameworks of uncertainty for genomic sequencing. Genetic counselors also perceived incongruencies between patients' and providers' expectations of genomic sequencing, which prompted them to modify patients' perceptions of uncertainty related to genomic sequencing. All genetic counselors agreed that guidance and strategies for genomic sequencing pretest counseling would be helpful, particularly for novice genetic counselors and non‐genetics providers. These findings highlight the need and potential for conceptual models of uncertainty and uncertainty management strategies to facilitate patient‐centered pretest counseling for genomic sequencing.